Children with sickle cell disease migrating to the United States from sub‐Saharan Africa. Issue 6 (8th February 2018) - Thornburg, Courtney D.; Ware, Russell E.
Abstract: Sickle cell disease (SCD) is an inherited red blood cell disorder that occurs worldwide and results in significant morbidity and mortality. In addition to affected children who are born in the US, an increasing number of children with SCD are migrating to the US with their families or through international adoption. Children arriving as immigrants or refugees have unique medical and psychosocial challenges that require a multidisciplinary team approach which takes into account the family's primary language, culture, and health beliefs. This review focuses on the special challenges for children with SCD who emigrate from sub‐Saharan Africa to the US.